2017
DOI: 10.1016/j.ecss.2017.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Seaweed beds support more juvenile reef fish than seagrass beds in a south-western Atlantic tropical seascape

Abstract: Seascape connectivity is regarded essential for healthy reef fish communities in tropical shallow systems. A number of reef fish species use separate adult and nursery habitats, and hence contribute to nutrient and energy transfer between habitats. Seagrass beds and mangroves often constitute important nursery habitats, with high structural complexity and protection from predation. Here, we investigated if reef fish assemblages in the tropical southwestern Atlantic demonstrate ontogenetic habitat connectivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 76 publications
0
38
0
Order By: Relevance
“…However, results from our experiment strongly support those observed from the initial sampling which covered similar depth ranges in both habitats, suggesting our findings were independent of depth. Indeed, macroalgal beds have been shown to support higher abundances of smaller fish species and juveniles (Eggertsen et al 2017) compared to unvegetated sediments (Guidetti 2000, Smith et al 2011.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, results from our experiment strongly support those observed from the initial sampling which covered similar depth ranges in both habitats, suggesting our findings were independent of depth. Indeed, macroalgal beds have been shown to support higher abundances of smaller fish species and juveniles (Eggertsen et al 2017) compared to unvegetated sediments (Guidetti 2000, Smith et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…For example, on subtidal rocky reefs the identity of habitats neighboring the brown macroalga, Sargassum linearifolium (coralline turfs or Caulerpa filiformis), altered the epifaunal community with some neighboring algae by acting as a dispersal barrier and reducing the connectivity of S. linearifolium patches for some species (Lanham et al 2015). In other vegetated marine habitats, epifauna can be exposed to higher predation by fish at patch edges in contrast to patch interiors and open sediments (Guidetti 2000, Smith et al 2011, while in macroalgal beds, smaller fish species and juveniles are more abundant within patches (Eggertsen et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found significantly greater numbers of juvenile fishes in Sargassum beds than in less structurally complex seagrass beds (Eggertsen et al 2017). A number of fish species recruit exclusively to seaweed beds (Wilson et al 2010;Hoey et al 2013;Fulton et al 2016), including species of commercial significance such as some Lethrinus spp.…”
Section: Ecological Role Of Macroalgae On Coral Reefsmentioning
confidence: 99%
“…In tropical coastal waters, various vegetation types, such as mangroves, seagrass beds, and seaweeds (henceforth referred to as "vegetative habitats"), offer valuable ecological functions. These habitats provide food, shelter, and physical links between back reef systems [1][2][3][4][5]. The trophic requirements of reef fishes, especially larger species, change over the course of development; many consequently undergo ontogenetic habitat shifts (reviewed by [6]).…”
Section: Introductionmentioning
confidence: 99%